PENGARUH INTERVENSI KETAHANAN KELUARGA ANTI NARKOBA TERHADAP PENINGKATAN KONDISI MENTAL EMOSIONAL PADA REMAJA - Saputri, Rivanny Yuliana; Laili, Nurfi (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
The role of the family is very important in the development of children, children and adolescents need loving attention and support from parents. The subjects in this intervention activity amounted to 10 students. Subjects were obtained using purposive sampling technique. The purpose of this study is to see the effectiveness of the intervention given to adolescents, who experience mental emotional problems in the poor category, as well as being able to develop adolescents' mental emotional conditions to be even better and know how to get out in bad conditions. This research is a quantitative experiment using the one group pre test post test design approach method by giving an initial measurement (pre-test) to the subject then given treatment and then carrying out the final measurement (post-test). Data collection uses a psychological scale with the Indonesian version of the Strength and Difficulties Quesstionnaire (SDQ) scale which has 25 items. The reliability test used Cronbach's Alpha technique with a result of 0, 773. Using the paired sample t - test, with the results of p = 0.034 (0.05). Based on the results of the study, the provision of family resilience interventions is considered effective and significant to overcome mental emotional problems in adolescents.